Mengorganisir Sampah yang Tercemar di TPS Masyarakat Dusun Karanglangon Desa Leran Wetan Kecamatan Palang Kabupaten Tuban - Zaimatul Utfa; Moh Anshori (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Waste is leftover material that is considered to have no economic value, but its existence cannot be avoided in people's social life. In Karanglangon Hamlet, the increase in population that occurs every year increases the volume of waste produced. As the population increases, household waste production and other activities also increase, thereby exacerbating waste management problems in the region. If not managed properly, the increasing amount of waste can have various negative impacts, both on public health and the surrounding environment, such as air, land and water pollution. This problem demands more attention from various parties to find appropriate and sustainable solutions. This research aims to identify in more depth the problems related to waste management at the Dusun Karanglangon TPS using the PAR (Participatory Action Research) approach method. The research results revealed that the condition of the waste at the TPS had a significant negative impact on the surrounding environment. The main causes are limited facilities, minimal budgets, and inadequate waste management standards, resulting in the accumulation of waste and increasingly severe environmental pollution.